Immunomodulatory and antioxidant potential of Asparagus racemosus Wild and Terminalia chebula Retz and their corresponding homeopathic mother tincture against canine demodicosis - SARKAR, TARUN KUMAR; DIMRI, UMESH; SHARMA, MAHESH CHANDRA (The Indian Journal of Animal Sciences, 2012)
A study was conducted to carry out the immunomodulatory and antioxidant potential of Asparagus racemosus and Terminalia chebula extracts and their corresponding homeopathic mother tincture (MT) on clinical cases of canine demodicosis. Alopecia, erythema, pustule/papules/vesicles, scale/excoriation/crust, hyperkeratinization and general appearance were the clinical manifestations of scoring demodicosed canine. The mean clinical scores were significantly higher in demodicosed canine than healthy dogs. The oral Asparagus racemosus extract or its homeopathy MT, in combination with amitraz dipping responded better in respect with the cellular and humoral immunities in demodicosed canine as compared with only amitraz dipping. In demodicosed canine there was increase in the level of lipid peroxidation in terms of malondialdehyde and the activity of superoxide dismutase and decrease in the activities of catalase and reduced glutathione in erythrocytes. The oral Terminalia chebula extract along with amitraz dipping exhibited maximum antioxidant activity in terms of reduced level of lipid peroxidation and activity of superoxide dismutase and increase activities of catalase and reduced glutathione in erythrocyte as compared with the decreasing orders of antioxidant activities of Asparagus racemosus extract, homeopathy Terminalia chebula MT and homeopathy Asparagus racemosus MT. In conclusion, demodicosis produced immunosuppression and oxidative stress in canine and for the treatment, amitraz dipping in combination with oral Asparagus racemosus extract responded better recovery.